Pengaruh Personal Selling, Publisitas Dan Promosi Penjualan Terhadap Minat Beli Produk Madu Trigona Montong Salut - Kusuma, Akla Triyan; Utami, Adinda Septi; P, Putra Abu Yazid; Yuliastuti, Tri (Universitas Mataram, 2024)
This study is entitled The Influence of Personal Selling, Publicity and Sales Promotion on Purchase Interest of Trigona Montong Salut Honey Products. The purpose of this study is to examine the Influence of Marketing Communications such as Personal Selling, Publicity and Sales Promotion on Purchase Interest of Trigona Montong Salut Honey Products. The type of research used is causal associative research, the location of the study was conducted in Salut Village, Montong Singgan Kayangan Hamlet, North Lombok Regency with a sample of 100 respondents who at least knew about Trigona Montong Salut Honey products. The data was then analyzed using multiple regression analysis. The data analysis technique used the SPSS version 23 program. The results of this study indicate that the form of Personal Selling Marketing Communication has a positive and significant effect on Purchase Interest with a significant value of 0.001 <0.05 and the form of Sales Promotion Marketing Communication has a significant positive effect on purchase interest with a significant value of 0.000 <0.05.